The Backward Design Learning Strategy Based on Literacy and Numeracy for Sociology Academic Ability Tests - Andhy Surya Hapsara; Lutfi Efendi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Education in Indonesia faces the crucial challenge of strengthening literacy and numeracy, especially in Sociology, a subject demanding data analysis and interpretation of social phenomena. This challenge is compounded by the need to prepare students for the Academic Ability Test (TKA), which emphasizes critical thinking and questions based on literacy-numeracy models.This best-practice research aims to implement the Backward design strategy integrated with literacy and numeracy to enhance the readiness of Grade XII students at SMAN 7 Yogyakarta for the Sociology TKA. The strategy was conducted through three stages: 1) Identify Desired Results (understanding TKA question formats); 2) Determine Acceptable Evidence (formative and summative assessments, including external Try Outs/TO); and 3) Design Learning Experiences (differentiated instruction and innovative activities like